The nearby spiral density‐wave structure of the Galaxy: Line‐of‐sight and longitudinal velocities of 61 masers - Griv, E.; Jiang, I.‐G.; Hou, L.‐G.; Ngeow, C.‐C. (Astronomische Nachrichten, 2017)
This paper is the eighth in a series presenting the results of the dynamical analysis of velocity fields of Galactic objects on the assumption that the system is subject to moderately unstable, low‐amplitude, tightly wound, and rigidly rotating Lin–Shu density waves. The data of 61 masers associated with star‐forming regions having distances d<4 kpc from the Sun and h<200 pc from the plane are collected from the work by Reid et al. Both line‐of‐sight vlos and transverse along the Galactic longitude vlvelocities of these objects are analyzed. It is shown that there may coexist at least two radial scales of irregularity of a velocity field with different wavelengths λ≈2 and λ≈3.5 kpc and amplitudes of the perturbed gravitational potential for all values of the number of spiral arms considered, m = 1, 2, 3, and 4. To be consistent with the current ideas as to the spiral structure of the Galaxy, we argue respectively that the Sun is located at the inner edge of the Cygnus–Orion arm (very close to the arm center), between the nearby inner Carina–Sagittarius and outer Perseus arms (closer to the inner one). Estimates obtained from an analysis of two independent velocities vlos and vl are fairly consistent. As for us, the latter establishes further evidence to support the Lin–Shu wave proposal.